Periodic discharges in veterinary electroencephalography—A visual review - Knipe, Marguerite F.; Bush, William W.; Thomas, Kristen E.; Williams, D. Colette (Frontiers in Veterinary Science, 2023)
First described in human EEG over sixty years ago, there are very few examples of periodic discharges in the veterinary literature. They are associated with a wide variety of etiologies, both intracranial and systemic, making interpretation challenging. Whether these patterns are indicative of ictal, interictal or postictal activity is a matter of debate and may vary depending on the clinical features in an individual patient. Periodic discharges have a repeated waveform occurring at nearly regular intervals, with varying morphology of individual discharges from simple sharp waves or slow waves to more complex events. Amplitudes, frequencies and morphologies of the discharges can fluctuate, occasionally evolving or resolving over time. This study presents a visual review of several veterinary cases with periodic discharges on EEG similar to those described in human EEG, and discusses the current known pathophysiology of these discharges.